Clausenawallines A and B, two new dimeric carbazole alkaloids from the roots of Clausena wallichii - Maneerat W. (2014)
Two new dimeric carbazole alkaloids, clausenawallines A and B, were isolated from the roots of Clausena wallichii. Their structures were elucidated by spectroscopic methods. Clausenawalline A was evaluated for its biological activities [anti-malaria (IC50 2.46 μg/mL), anti-TB (MIC 12.50 μg/mL)] and cytotoxicity against three human cancer cell lines [KB (IC 50 7.87 μg/mL), MCF7 (IC50 25.43 μg/mL), and NCI-H187 (IC50 10.97 μg/mL)]. © 2011 Elsevier Ltd. All rights reserved.